PO.6.141 Efficacy of mycophenolate mofetil (MMF) in pediatric patients with defined and undefined type I interferonopathies. (27th September 2022) - Natale, MF; Udina, C; Raffaele, CGL; Messia, V; Celani, C; Bracaglia, C; Federici, S; Prencipe, G; De Benedetti, F; Insalaco, A
Abstract : Purpose: Interferonopathies are conditions characterized by excessive production of type 1 interferon. Several diseases, autoinflammatory or autoimmune, are classified as type1 interferonopathies such as Aicardi-Goutieres, Sting associated vasculopathy with onset in Infancy, monogenic Systemic lupus erythematosus (SLE) and Dermatomyositis. The aim of this study is to evaluate the role of MMF in modulating the activation of the interferon pathway describing its clinical and laboratory effects in a cohort of patients with defined and undefined interferonopathy Methods: We included patients aged 0–18 years with defined (genetically confirmed) and undefined interferonopathy (evocative clinical picture, interferon signature (IS)> 2 in at least 3 samples 3 months apart, negative genetic test) followed at Bambino Gesù Children's Hospital treated with MMF. For each patient demographic, clinical, laboratory parameters and IS were collected every 3 months starting from the year before the MMF treatment until the date of the last follow up. In vitro the effect of MMF on the IFN-pathway was evaluated by adding MMF to peripheral mononuclear cells of the patients. Results: Nine patients were enrolled, 4 with defined and 5 with undefined interferonopathy. When therapy was started, 78% of patients had recurrent febrile episodes, 57% polyarthritis, 67% skin and/or neurological involvement. A pathological brain MRI was found in 44% of patients. Persistent anemia, lymphopenia and autoantibody positivity were detected in 44% of patients and increased ESR in 67%. All patients had a positive IS(median 46.9; IQR 23.5–133.8). Three months after the beginning of MMF we observed a resolution of febrile episodes and skin manifestations in 86% of cases, remission of joint involvement in all patients, improvement of neurological symptoms in 1 patient, resolution of the anemia and normalization of the ESR in 50% and 66% respectively. During MMF therapy, as reported in patients with SLE, ANA titers decline or normalized in 75% of patients and anti dsDNA in 66% of patients. Cerebral MRI improved in patient with radiological alterations. MMF therapy allowed to completely withdraw glucocorticoid therapy in 4 patients and to reduce the dosage in other 3. No significant reduction in IS was detected during a median follow-up of 36 months (IQR 25–45). Nevertheless these data contrasted with our ex vivo experiments in which the incubation with MMF of peripheral mononuclear cells of our patients (and of patients with other interferonopathies including SLE and dermatomyositis) showed a significant reduction in the INF-a pathway activation after cells stimulation Conclusions: This is the first study evaluating the effects of MMF in a cohort of patients with type I interferonopathy. The results, although preliminary, seem to suggest a role of the drug in improving clinical, laboratory and radiological findings of our patients, allowing also a significant glucocorticoid sparing. These data, if confirmed in larger and prospective studies, should encourage the use of MMF especially for those patients in which standard treatment with JAK inhibitor could be contraindicated or ineffective